Autoimmune/inflammatory syndrome induced by adjuvants in a woman with Hashimoto thyroiditis and familial autoimmunity—a case report and literature review - Plavsic, Aleksandra; Arandjelovic, Snezana; Dimitrijevic, Milan; Kusic, Natasa; Tomic Spiric, Vesna; Popovic, Bojana; Jovicic, Zikica; Peric Popadic, Aleksandra; Miskovic, Rada (Frontiers in Immunology, 2023)
Introduction Autoimmune/inflammatory syndrome induced by adjuvants (ASIA) consists of a wide spectrum of symptoms and immunological features that are believed to develop in predisposed individuals after exposure to an adjuvant, including a silicone breast implant (SBI). Different autoimmune diseases (AIDs) have been associated with ASIA, but ASIA development after SBI in women with Hashimoto thyroiditis (HT) and familial autoimmunity has rarely been described. Case report A 37-year-old woman presented in 2019 with arthralgia, sicca symptoms, fatigue, + antinuclear antibody (ANA), + anti SSA, and + anticardiolipin Immunoglobulin G (IgG) antibodies. She was diagnosed with HT and vitamin D deficiency in 2012. The familial autoimmunity was present: the patient’s mother had been diagnosed with systemic lupus erythematosus and secondary Sjogren’s syndrome and her grandmother with cutaneous lupus and pernicious anemia. In 2017, the patient had a cosmetic SBI procedure that was complicated by repeated right breast capsulitis. After 2 years of irregular visits due to COVID-19, she presented with + ANA, + anticentromere antibodies both in sera and seroma, sicca syndrome, arthralgias, twinkling in extremities, abnormal capillaroscopic findings, and reduced diffusing capacity of the lungs for carbon monoxide. She was diagnosed with ASIA, and antimalarial and corticosteroid therapy were introduced. Conclusion In patients with HT and familial autoimmunity, SBI should be carefully considered due to the possibility of ASIA development. Hashimoto thyroiditis, familial autoimmunity, and ASIA seem to be interconnected in the complex mosaic of autoimmunity in predisposed individuals.